Genomic fingerprinting of penicillinase-producing strains of Neisseria gonorrhoeae in Valencia, Spain. Issue 3 (June 1992) - Dasi, M A; Nogueira, J M; Camarena, J J; Gil, C; García-Verdú, R; Barberá, J L; Barberá, J
Abstract : OBJECTIVE--To compare the value of different markers and their combinations with the restriction enzyme technique in the differentiations of penicillinase-producing N. gonorrhoeae (PPNG) strains. MATERIALS AND METHODS--17 PPNG strains isolated from symptomatic, untreated male patients with urethritis were characterised by antibiotic sensitivity testing, auxotyping, serotyping, plasmid profile, and restriction endonuclease fingerprinting (Hind III digestion). Cluster analysis with the method of unweighted pair-group average (UPGMA) linkage was used to calculate similarity or dissimilarity for PPNG strains. MAIN RESULTS--Either auxotyping or plasmid profile alone differentiated three groups of PPNG strains, whereas the combination auxotyping/serotyping identified 10. Although the combination auxotyping/serotyping/plasmid profile and the restriction enzyme technique showed a similar discrimination ability (differentiation of 11 PPNG strains), genomic fingerprinting gave highly specific restriction patterns on individual gonococcal isolates. CONCLUSIONS--The combination of different markers gave more epidemiological information than the use of only one. The sequence of discriminating ability for PPNG strains was: auxotyping/serotyping less than auxotyping/serotyping/plasmid profile less than restriction patterns of genomic DNA.